PREVENTION AND TREATMENT OF VITAMIN D DEFICIENCY: CURRENT LOOK AT THE ISSUE - Yu. S. Lashkova (Union of pediatricians of Russia, 2015)
The article presents the current data on the metabolism of vitamin D and its role in the development of bone tissue in children and the further condition thereof. Natural vitamin D sources, as well as the current routine practice of preventing deficiency of this organic substance are unable to fully satisfy a child's demand for this vitamin, which is why recommendations on vitamin D intake ought to be revised. The article details schedules for prescription of vitamin D for preventing and treating the body deficiency thereof based on results of the studies completed in the recent years. The role of the main marker enabling assessing vitamin D concentration in the body - 25(OH)D - the reference values whereof are yet to be commonly established has been analyzed. The article lists recommendations on rickets prevention and treatment in children. The article presents data on the possible mechanisms of development of toxic effects in the setting of vitamin D intake.